2020
DOI: 10.1007/s00414-020-02394-x
|View full text |Cite
|
Sign up to set email alerts
|

Post-mortem genetic investigation of cardiac disease–associated genes in sudden infant death syndrome (SIDS) cases

Abstract: The sudden infant death syndrome (SIDS) is one of the leading causes of postneonatal infant death. It has been shown that there exists a complex relationship between SIDS and inherited cardiac disease. Next-generation sequencing and surveillance of cardiac channelopathy and cardiomyopathy genes represent an important tool for investigating the cause of death in SIDS cases. In the present study, targeted sequencing of 80 genes associated with genetic heart diseases in a cohort of 31 SIDS cases was performed. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…In 3.5% of the SIDS cases, a genetic polymorphism in a cardiac myopathy gene was reported (145). Although it is very important to detect and evaluate the genetic variants in order to counsel the family in a SIDS case, but it should be evaluated and labeled carefully as "pathogenic" or "informative" as 4.3% was found to be pathogenic and 13% as informative in the recent study mentioned above (143) which is much lower that assumed previously.…”
Section: Discussionmentioning
confidence: 80%
“…In 3.5% of the SIDS cases, a genetic polymorphism in a cardiac myopathy gene was reported (145). Although it is very important to detect and evaluate the genetic variants in order to counsel the family in a SIDS case, but it should be evaluated and labeled carefully as "pathogenic" or "informative" as 4.3% was found to be pathogenic and 13% as informative in the recent study mentioned above (143) which is much lower that assumed previously.…”
Section: Discussionmentioning
confidence: 80%
“…Previous studies have reported genetic diseases in 13% to 75% of infant deaths in various subpopulations with various genetic tests. [15][16][17][18][19][20][21][22][23][24][25][26] However, most of these studies were small, limited to SIDS, and used exome sequencing, and all were retrospective. In the current study, all infant deaths were examined by WGS, and most were prospectively followed since ICU admission.…”
Section: Discussionmentioning
confidence: 99%
“…The DNA of all cases was analyzed for sequence variations using the TruSight cardio panel (Illumina) consisting of 174 genes with known cardiac associations. Paired-end libraries were prepared following the manufacturer’s protocol Nextera™ Flex for Enrichment as described previously [ 18 , 19 ]. Sequencing was performed on the Illumina® MiniSeq™ system (2 × 150 bp paired end reads).…”
Section: Methodsmentioning
confidence: 99%